Role of Platelet-Derived Growth Factor (PDGF) in Asthma as an Immunoregulatory Factor Mediating Airway Remodeling and Possible Pharmacological Target - Kardas, Grzegorz; Daszyńska-Kardas, Agnieszka; Marynowski, Mateusz; Brząkalska, Oliwia; Kuna, Piotr; Panek, Michał (Frontiers in Pharmacology, 2020)
Asthma is a chronic and hetereogenic disease of the respiratory system, one of the most common lung diseases worldwide. The underlying pathologies, which are chronic inflammatory process and airway remodeling (AR), are mediated by numerous cells and cytokines. Particularly interesting in this field is the platelet-derived growth factor (PDGF), one of the members of the human growth factor family. In this article, the authors analyze the available data on the role of PDGF in asthma in experimental models and in human research. PDGF is expressed in airway by various cells contributing to asthma pathogenesis – mast cells, eosinophils, airway epithelial cells. Research confirms the thesis that this factor is also secreted by these cells in the course of asthma. The main effects of PDGF on bronchi are the proliferation of airway smooth muscle (ASM) cells, migration of ASM cells into the epithelium and enhanced collagen synthesis by lung fibroblasts. The importance of AR in asthma is well recognized and new therapies should also aim to manage it, possibly targeting PDGFRs. Further studies on new and already existing drugs, mediating the PDGF signaling and related to asthma are necessary. Several promising drugs from the TKI group, including nilotinib, imatinib masitinib and sunitinib, are currently being clinically tested and other molecules are likely to emerge in this field.